College physics : reasoning and relationships - Giordano, Nicholas J., author 395857 (Boston, MA : Cengage Wadsworth, 2013)
Master the fundamental concepts of physics with COLLEGE PHYSICS: REASONING AND RELATIONSHIPS. The theme of Reasoning and Relationships is reinforced throughout the book, helping you master these concepts, apply them to solve a variety of problems, and appreciate the relevance of physics to your career and your everyday life. By understanding the reasoning behind problem solving, you learn to recognize the concepts involved, think critically about them, and move beyond merely memorizing facts and equations.